2022
DOI: 10.3390/reports5020013
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate-Induced Suicidal Ideation and Olfactory Hallucinations: A Case Report

Abstract: Antiepileptic drugs prescribed in the context of migraine have been reported to be potentially linked with an increased risk of suicidal ideation and behavior. Meta-analyses support the evidence that amongst antiepileptic drugs, Topiramate has the greatest potential for facilitating the occurrence of suicidal ideation and behavior. Studies indicate that this occurs via the increased incidence of mood disorders amongst the population with migraines using Topiramate as a treatment, with a slow and progressive on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Particular attention has been also given to topiramate: several studies indicated its efficiency in such disorders as trichotillomania, excoriation disorder and NSSI [68]. However, a recent case report revealed that the use of topiramate may be associated with drug-induced suicidal ideation [69].…”
Section: Other Agentsmentioning
confidence: 99%
“…Particular attention has been also given to topiramate: several studies indicated its efficiency in such disorders as trichotillomania, excoriation disorder and NSSI [68]. However, a recent case report revealed that the use of topiramate may be associated with drug-induced suicidal ideation [69].…”
Section: Other Agentsmentioning
confidence: 99%